(untitled) (Al-Academy, 2016)
The magazine is one of the print media , which represents an important gateway to the wider world , due for its intellectual and cultural fun for the recipient affecting the everyday needs him in various directions . The cover of the magazine is the owner of appearance and impact of the first look the magazine , including the magnitude of the value of the functional and aesthetic pay the reader to the acquisition, as it seeks designed to attract the receiver and achieve better grades optical communication enabled this diversity vocabulary construction for the cover of the magazine and consistent with the idea of design .Ensure Current search four chapters , first chapter of which , the research problem and was questioning following what the role of diversity formal in promoting infrastructure design for the cover of the magazine ? , And the importance that the possibility of enriching the knowledge and skills of designers and specialists in the field of design, layout , and can be represented by adding a scientific for the library design . was the goal of research ( known diversity of formal structure designs magazine covers Arabic). either limits Search: border objectivity : Diversity formal structure designs covers the front of magazines (released the cover ), and the border spatial : magazines specialized in women’s affairs and issued in the states Arabian Gulf , while the border temporal : the first three months of 2013 being the year the preparation of research. the second chapter has included three sections : eat first section brief summary of diversity and unity , diversity and methods directorial for the cover of the magazine and also included the diversity of systems and foundations and relationships design , The second topic addressed the concept of shape and design elements of the structure for the cover of the magazine and included the name of the magazine and the date line and color , cover Anwanat and cartoon pictures. And then was extracted indicators that resulted from the theoretical framework as scientific reported them in Procedures and method discussed in the analysis of the content of the samples, as the researcher chose this method to fit the procedural stages in the analysis.And dealt with ( research procedures ) five samples describes the research and analysis, either the fourth quarter has included a presentation of the results of the researcher ’s findings , conclusions and proposals and recommendations